New perspectives in the management of low-risk thyroid cancer. Experience with thyroid lobectomy in a cohort of 114 patients (Revista Argentina de Cirugía, 2026)
Background: The treatment of low-risk differentiated thyroid cancer (DTC) is still a matter of debate. Over the past few decades, there has been a shift towards a more personalized approach, tailored to the individual risks of each patient and tumor. The current practice guidelines recommend lobectomy in selected patients, with low risk of recurrence.Objective: To describe the results of thyroid lobectomy in a cohort of patients with DTC with low risk of recurrence.Material and methods: We conducted a descriptive and observational study. The medical records of patients with DTC who underwent thyroid lobectomy between January 2015 and April 2023 were retrospectively reviewed.Results: A total of 114 patients were operated on; mean age was 44 ± 12 years and 90 (79%) were women. The median tumor size was 9.4 mm (IQR 25-75% 7-13 mm), and 103 nodules (90%) were solid on ultrasound. Only 2 patients with vascular invasion involving > 4 vessels required completion thyroidectomy. There were no major complications and only one patient developed temporary recurrent laryngeal palsy. There were no locoregional or distant recurrences during mean follow-up of 33.4 months.Conclusion: Thyroid lobectomy for low-risk DTC had low morbidity and no recurrences in the series presented. The rigorous selection of patients and the interaction of a multidisciplinary team are considered essential for the successful implementation of this therapeutic approach.
Keywords: thyroid carcinoma; low risk; thyroid lobectomy; recurrence risk; ultrasound imaging; patient selection